2011
DOI: 10.1128/jvi.05265-11
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Anticytomegalovirus Compound AIC246 (Letermovir) Inhibits Human Cytomegalovirus Replication through a Specific Antiviral Mechanism That Involves the Viral Terminase

Abstract: Human cytomegalovirus (HCMV) remains the leading viral cause of birth defects and life-threatening disease in transplant recipients. All approved antiviral drugs target the viral DNA polymerase and are associated with severe toxicity issues and the emergence of drug resistance. Attempts to discover improved anti-HCMV drugs led to the identification of the small-molecular-weight compound AIC246 (Letermovir). AIC246 exhibits outstanding anti-HCMV activity in vitro and in vivo and currently is undergoing a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
241
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(253 citation statements)
references
References 50 publications
4
241
0
5
Order By: Relevance
“…Moreover, viral protein pp65 has been reported to initially localize at the nucleus of the infected cells and at later times of infection both at the nucleus and the cytoplasm, at the viral AC compartment. 11,50,52 Upon GCV treatment, residual pUL32 and pp65 proteins that are expressed, 62,63 are restricted to their nuclear localization (Fig. 5, g,i and p,r).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, viral protein pp65 has been reported to initially localize at the nucleus of the infected cells and at later times of infection both at the nucleus and the cytoplasm, at the viral AC compartment. 11,50,52 Upon GCV treatment, residual pUL32 and pp65 proteins that are expressed, 62,63 are restricted to their nuclear localization (Fig. 5, g,i and p,r).…”
Section: Discussionmentioning
confidence: 99%
“…Additional therapeutics have been developed, including the terminase inhibitor letermovir and at least one neutralizing monoclonal antibody against gH. However, resistance against these compounds has been generated in laboratory experiments (5,53), reinforcing the need to design therapeutics with reduced probability of resistance. The current study has revealed the existence of small, highly conserved, and thus likely highly constrained, sites across the HCMV genome, thereby highlighting potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Member of the new antiviral class of quinazolines, it acts after viral DNA synthesis by inhibiting the subunit protein pUL56 that, together with pUL89, is a key element of the enzyme complex named terminase, [72,73] directly involved in the cleavage and package of viral DNA chains in the virionic capside [74,75]. Because of its distinct mechanism of action, it does not show cross-resistance with other antiviral drugs and there are reports of clinically relevant activity against GCV-, FOS-and CDF-resistant CMV strains [76,77].…”
Section: Letermovir -The Terminasetormentioning
confidence: 99%